2016
DOI: 10.31580/jmi.v11i1.56
|View full text |Cite
|
Sign up to set email alerts
|

Do Intrinsic and Extrinsic Rewards influence the Job satisfaction and Job performance? Mediating Role of Reward System

Abstract: Now a day’s firms are striving to achieve competitive advantage by using different strategic techniques. As a result of high competitive pressure; firms are making struggle to get competitive edge by utilizing workers’ talent, abilities and proficiency to formulate the accurate exploitation of employees’ works organization offer different benefits, rewards schemes. Satisfied employees becoming more devoted dedicate and attached with their organization as compared to other employees. The main purpose of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
(8 reference statements)
0
13
0
4
Order By: Relevance
“…First, the previous study showed that a reward management system can significantly influence a workforce and can be motivated to improve their efforts and performance (Rai et al, 2018), and therefore, different rewards have been employed to measure performance such as monetary reward (Aguinis et al, 2013), remuneration (Calvin, 2017), and enough pay and bonus (Pouliakas, 2010); hence, we indicated intrinsic reward for measuring employee performance. Second, only a few studies discovered the relationship between intrinsic reward and employee performance and used some mediators such as organizational commitment (Taba, 2018) and reward system (Riasat et al, 2016), but no study has employed employee motivation as mediators. Third, very limited research has been performed to examine intrinsic reward-the performance of the employee in the Pakistan context by using mediating mechanisms, but no study has explored that in SMEs.…”
Section: Discussionmentioning
confidence: 99%
“…First, the previous study showed that a reward management system can significantly influence a workforce and can be motivated to improve their efforts and performance (Rai et al, 2018), and therefore, different rewards have been employed to measure performance such as monetary reward (Aguinis et al, 2013), remuneration (Calvin, 2017), and enough pay and bonus (Pouliakas, 2010); hence, we indicated intrinsic reward for measuring employee performance. Second, only a few studies discovered the relationship between intrinsic reward and employee performance and used some mediators such as organizational commitment (Taba, 2018) and reward system (Riasat et al, 2016), but no study has employed employee motivation as mediators. Third, very limited research has been performed to examine intrinsic reward-the performance of the employee in the Pakistan context by using mediating mechanisms, but no study has explored that in SMEs.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Deeprose (1994) argued that providing effective recognition to employees can enhance their motivation and productivity together the result of which is the performance increasing for the company. Fostering learning opportunity through training program as well as seminars, workshop, conference is more meaningful to them for effective achievement (Riasat et al 2016).…”
Section: Extrinsic and Intrinsic Rewardsmentioning
confidence: 99%
“…Spector (1997) argues that job satisfaction illustrates how well employees are happy with their work. If employees have positive feelings towards work, employees will have a higher level of satisfaction with their work (Nisar, Riasat, & Aslam, 2016). In line with Mahardiana and Thahir (2019) based on the findings in the assessment, to improve employee performance, it can support managers to assist the organization by paying attention to employee competencies.…”
Section: Resultsmentioning
confidence: 60%